A mechanism of cohesin‐dependent loop extrusion organizes zygotic genome architecture. (7th December 2017) - Gassler, Johanna; Brandão, Hugo B; Imakaev, Maxim; Flyamer, Ilya M; Ladstätter, Sabrina; Bickmore, Wendy A; Peters, Jan‐Michael; Mirny, Leonid A; Tachibana, Kikuë
Abstract: Fertilization triggers assembly of higher‐order chromatin structure from a condensed maternal and a naïve paternal genome to generate a totipotent embryo. Chromatin loops and domains have been detected in mouse zygotes by single‐nucleus Hi‐C (snHi‐C), but not bulk Hi‐C. It is therefore unclear when and how embryonic chromatin conformations are assembled. Here, we investigated whether a mechanism of cohesin‐dependent loop extrusion generates higher‐order chromatin structures within the one‐cell embryo. Using snHi‐C of mouse knockout embryos, we demonstrate that the zygotic genome folds into loops and domains that critically depend on Scc1‐cohesin and that are regulated in size and linear density by Wapl. Remarkably, we discovered distinct effects on maternal and paternal chromatin loop sizes, likely reflecting differences in loop extrusion dynamics and epigenetic reprogramming. Dynamic polymer models of chromosomes reproduce changes in snHi‐C, suggesting a mechanism where cohesin locally compacts chromatin by active loop extrusion, whose processivity is controlled by Wapl. Our simulations and experimental data provide evidence that cohesin‐dependent loop extrusion organizes mammalian genomes over multiple scales from the one‐cell embryo onward. Synopsis: Zygotic genomes fold into loops and domains that depend on cohesin and are regulated in size by Wapl. Single‐nucleus Hi‐C and polymer models of chromosomes provide evidence for cohesin‐dependent loop extrusion organizing genomes over multiple scales. Zygotic genomes are organized into cohesin‐dependent chromatin loops and Topologically Associating Domains (TADs). Loop extrusion leads to different loop strengths in maternal and paternal genomes. Cohesin restricts inter‐chromosomal interactions by altering chromosome surface area. Loop extrusion organizes chromatin at multiple genomic scales. Abstract : Single‐nucleus Hi‐C and microscopy show that the zygotic genome folds into loops and domains in a cohesin‐dependent manner with differences in maternal and paternal chromosome organization.